Informal agreements and quasi-legal mechanisms in EU-Africa cooperation on migration: how the EU takes advantage of the GCM commitments - Frasca, Eleonora (Frontiers in Human Dynamics, 2023)
Soft law plays an increasing role in EU external migration law, particularly in the context of EU-Africa cooperation on migration. A legal-analytical inquiry into the formats and functions of soft law, based on the example of EU-Africa cooperation on migration, reveals that the EU preference for soft law is functional to achieve the EU's own migration objectives in Africa, namely preventing and containing irregular migration, rather than facilitating mobility, as envisaged in the UN Global Compact for Migration. This article presents and discusses the formats of soft law in EU-Africa cooperation, distinguishing between informal agreements and quasi-legal mechanisms for cooperation, and their respective para-law and pre-law functions. It then suggests that while informal agreements set the broad objectives of international cooperation and prepare the ground for legal changes in third countries, quasi-legal mechanisms for cooperation guarantee their implementation. Their combined effects ignite broader processes of domestic reforms in the African States through a technique of legal influence.1 As Chetail notes, "the current international legal framework governing migration consists of an eclectic set of superimposed norms that are scattered throughout a vast number of overlapping fields" (Chetail, 2020, p. 6). Within the UN framework, the UN conventions concern refugees, migrant workers and trafficked or smuggled migrants. He also notes that "the rapid growth of multilateralism in an area that has long been associated with domestic jurisdiction has been possible through the proliferation of non-binding instruments and consultative processes during the last three decades […]. Although its influence is not free from ambiguities, the unprecedented expansion of soft law has been decisive in building confidence and creating a routine of intergovernmental dialogue" (Chetail, 2020, p. 283).